2006
DOI: 10.1152/ajpgi.00155.2005
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic pharmacokinetics of propranolol in rats with adjuvant-induced systemic inflammation

Abstract: Systemic inflammation is known to affect drug disposition in the liver. This study sought to relate and quantitate changes in hepatic pharmacokinetics of propranolol with changes in hepatic architecture and physiology in adjuvant-treated rats. Transmission electron microscopy was used to assess morphological changes in mitochondria and lysosomes of adjuvant-treated rat livers. The disposition of propranolol was assessed in the perfused rat liver using the multiple indicator dilution technique. Hepatic extracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 39 publications
3
27
0
1
Order By: Relevance
“…Hepatocyte permeability, intrinsic metabolic clearance, ion trapping, and microsomal binding were all changed in diseased livers (Siebert et al, 2004). An altered hepatic cytochrome P450 (P450) concentration was also seen in adjuvant-induced systemic inflammation (Hung et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Hepatocyte permeability, intrinsic metabolic clearance, ion trapping, and microsomal binding were all changed in diseased livers (Siebert et al, 2004). An altered hepatic cytochrome P450 (P450) concentration was also seen in adjuvant-induced systemic inflammation (Hung et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Their concentrations were increased in case of group II, III and VI animals (results have not shown here). Due to arthritis, walls of liver become leaky therefore enzyme concentration in arthritic condition increases [21,22]. Histopathological analysis of liver corroborated these findings.…”
Section: Discussionmentioning
confidence: 85%
“…Inflammation in an organ may affect the overall homeostasis of the body. Studies have suggested that during inflammatory diseases, serum aspartate aminotransferase (AST) and alanine aminotransferase (ALT) increases [21], [22]. These enzymes assays are good indices of liver damage.…”
Section: Discussionmentioning
confidence: 99%
“…NSAIDs.] At yet another level, adjuvant treatments can systemically alter membrane transport of a drug into hepatocytes [34].…”
Section: Conditional Pharmacologymentioning
confidence: 99%
“…Mycobacterial adjuvants also perturb iron distribution most notably in the liver [34]. An excess of ferritin accumulates, anaemia may ensue, and the production of some ironcontaining cytochromes is compromised.…”
Section: Conditional Toxicologymentioning
confidence: 99%